A note on linear preservers of singular matrices - Huat, Lim Ming (Malaysian Journal of Science, 1995)
We give a simple proof of a result of Laffey and Loewy concerning linear mappings on n x n matrices over an infinite field that preserve singular matrices as well as its extension to finite fields with at least n + 1 elements.